Pengembangan Trainer Smart Building Pada Mata Pelajaran Instalasi Penerangan Listrik - Lufthi Hamdi Saputra; Taali Taali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research aims to develop trainer learning media in portable form on the subject of electrical lighting installation, as well as evaluate its validity, practicality, and effectiveness. This learning media is designed with the aim of increasing interaction between teachers and students so that the learning process is active, effective, and efficient. This research is an implementation of research and development (R&D) methods in developing learning media for electrical lighting installation subjects. By using the 4D development method which involves a series of steps from the define, design, develop, and disseminate stages. The data collected is primary in nature, originating from the participation of expert lecturers, teachers, and students to evaluate the validity, practicality, and effectiveness of the learning media developed. Through this method, this research produces in-depth insights regarding the use of learning media in the context of learning electrical lighting installations. The results obtained from this research and development are as follows: the validity results obtained from the lecturer's assessment are declared valid, the results from practicality testing obtained from the average of teacher practicality and student practicality are in the very practical category, and the effectiveness value of media trainer testing Smart buildings fall into the effective category.